Structural changes in needle epicuticular waxes of Balkan Abies species in relation to natural weathering - Nikolić, Jelena S.; Miljković, Miroslav S.; Zlatković, Bojan K.; Nikolić, Biljana M.; Mitić, Zorica S. (Iheringia, Série Botânica., 2024)
This study represents the first survey of the structural changes of epicuticular waxes of Abies alba, A. x borisii-regis and A. cephalonica in relation to natural weathering. In all three studied species, epicuticular wax on the adaxial side of the needles was in the form of granules, whose amount increased with age of needles, so they were most prominent on the oldest needles. The main wax crystalloids on the abaxial needle surfaces were tubules with a tendency to concentrate within the stomatal complexes and between them in the stomatal rows. As the tubules aged they generally tended to agglomerate and fuse, forming amorphous wax crusts. Although we did not find differences in the micromorphology types of epicuticular wax among the examined species, both the tendency of amount of granules to increase and the degree of degradation of tubules into amorphous crusts as the result of natural ageing process were well-documented.